2007
DOI: 10.1007/bf03405439
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Medication Use Among Women Survivors of Intimate Partner Violence

Abstract: Objective: Our objective was to describe patterns of medication use in a convenience sample of 309 women with a history of intimate partner violence (IPV) participating in a study of women's health after leaving an abusive partner (WHES). Methods: Using data collected through interviews and health assessments, frequencies of past-month use of medications; abuse experienced, health problems and medical diagnoses; and selected demographics were calculated. Associations among abuse history, employment status, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 12 publications
4
35
0
5
Order By: Relevance
“…It substantiates previous cross-sectional findings of increased medication use among women exposed to IPV5 6 11 14 and adds new evidence about restricted drugs with verified addictive potential. Our sample was enrolled from a large-scale survey with consent to link information to health registers.…”
Section: Discussionsupporting
confidence: 86%
“…It substantiates previous cross-sectional findings of increased medication use among women exposed to IPV5 6 11 14 and adds new evidence about restricted drugs with verified addictive potential. Our sample was enrolled from a large-scale survey with consent to link information to health registers.…”
Section: Discussionsupporting
confidence: 86%
“…Depression was the most commonly researched aspect of mental health in relation to intimate partner violence, being reported on in 42 of the reviewed articles [10, 1353]. The high relative importance of depression in its impact on health, as a result of IPV, is shown by the burden of disease figures given in the study by Vos et al [46] who found that 34.7% of the total IPV disease burden was attributable to depression.…”
Section: Health Outcomesmentioning
confidence: 99%
“…In this review, anxiety was investigated as a part of sixteen studies [1315, 20, 22, 25, 28, 31, 37, 39, 40, 43, 46, 50, 51, 53], but it was not the exclusive focus of any of these studies, usually being reported along with other common mental disorders, most often depression. In the study on burden of disease associated with IPV, Vos et al [46] found that 27.3% of the total IPV burden of disease was attributable to anxiety, making it the second highest contributing factor, with only depression having a higher percentage score.…”
Section: Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aftermath of IPV, women continue to suffer from disabling mental and physical health problems related to IPV, such as PTSD, depression, sleep disturbances, fatigue, gastrointestinal disorders, chronic pain, and hypertension (Adkins & Kamp Dush, 2010;Fishman, Bonomi, Anderson, Reid, & Rivara, 2010;Humphreys & Lee, 2005;Wuest et al, 2007). Based on a review of the published literature, D. Anderson and Saunders (2003) concluded that, after separation, women's mental health problems, particularly depression and PTSD, might be equal to or exceed the problems they experience before leaving the relationship.…”
Section: Intrusion Associated With Mental and Physical Health Problemsmentioning
confidence: 99%